Law and language - Bhatnagar, R.P. (Delhi, 1985)
This is an anthology of English for law students written according to the new law courses devised by the Bar Council of India and accepted by a large number of universities in India. The anthology has been prepared by two leading ELT specialists and edited by Dr Madhava Menon, Secretary, Bar Council of India, and Professor of Law, Delhi University. Each passage has brief notes on pronun ciation, spelling, vocabulary, comprehension, composition, precis and letter writing. The introductory section consists of a general note on these basic requirements which is followed by some of the finest writings by leading jurists on law.
Keywords: Law Language